2022
DOI: 10.1021/acschembio.2c00273
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Alterations of a Protein Hub Produce Divergent Effects within a Binding Site

Abstract: Progress in tumor sequencing and cancer databases has created an enormous amount of information that scientists struggle to sift through. While several research groups have created computational methods to analyze these databases, much work still remains in distinguishing key implications of pathogenic mutations. Here, we describe an approach to identify and evaluate somatic cancer mutations of WD40 repeat protein 5 (WDR5), a chromatin-associated protein hub. This multitasking protein maintains the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In addition, it has been shown that the Win site mediates transient PPIs with dozens of proteins, including those involved in key signaling pathways, such as phosphatidylinositol 3-kinase (PI3K) and 3-phosphoinositide-dependent protein kinase 1 (PDPK1). 84 Interestingly, a high-density distribution of missense somatic cancer mutations of WDR5 occurs within and around the Win site, 85 some of which significantly alter the strength of the MLL-WDR5 interactions. 78,83,86,87 On the opposite side of the Win site, WDR5 includes the WBM binding site.…”
Section: Comparisons Between Myc W B M −Wdr5 and Mll4mentioning
confidence: 99%
“…In addition, it has been shown that the Win site mediates transient PPIs with dozens of proteins, including those involved in key signaling pathways, such as phosphatidylinositol 3-kinase (PI3K) and 3-phosphoinositide-dependent protein kinase 1 (PDPK1). 84 Interestingly, a high-density distribution of missense somatic cancer mutations of WDR5 occurs within and around the Win site, 85 some of which significantly alter the strength of the MLL-WDR5 interactions. 78,83,86,87 On the opposite side of the Win site, WDR5 includes the WBM binding site.…”
Section: Comparisons Between Myc W B M −Wdr5 and Mll4mentioning
confidence: 99%
“…To appraise our attempt at a better understanding of these nanopores, we utilized a recently developed sensing platform that detects WD40 repeat protein 5 (WDR5), a chromatin-associated hub. The 334-residue highly conserved WDR5 plays an essential role in the regulatory mechanisms of histone 3 lysine 4 (H3K4) mono- and dimethylation. All our engineered nanopore sensors are equipped with a 14-residue WDR5 interaction (Win) motif ligand , of mixed-lineage leukemia 4 (MLL4 Win ) (Figure b and Table S1 in the Supporting Information). MLL4 is a member of the human MLL/SET1 methyltransferase family .…”
mentioning
confidence: 99%
“…The 334-residue highly conserved WDR5 plays an essential role in the regulatory mechanisms of histone 3 lysine 4 (H3K4) mono- and dimethylation. 81 84 All our engineered nanopore sensors are equipped with a 14-residue WDR5 interaction (Win) motif ligand 60 , 85 of mixed-lineage leukemia 4 (MLL4 Win ) ( Figure 1 b and Table S1 in the Supporting Information). MLL4 is a member of the human MLL/SET1 methyltransferase family.…”
mentioning
confidence: 99%